Reassessing Qualitative Self-Assessments and Experimental Validation - Jonathan Chapman; Pietro Ortoleva; Erik Snowberg; Leeat Yariv; Colin Camerer (CESifo GmbH, 2025)
Qualitative self-assessments of economic preferences have recently gained popularity, often supported by experimental validation, a method that links them to choices in incentivized elicitations. We illustrate theoretically that experimental validation may fail to produce reliable new measures. Empirically, analyzing data from over 13,000 participants across diverse samples, we document four key findings. First, qualitative self-assessments and traditional incentivized measures exhibit weak correlations, even when accounting for response noise. Second, qualitative self-assessments sometimes correlate more strongly with theoretically distinct incentivized elicitations than those for which they are intended to proxy. Third, relationships between qualitative self-assessments and various attributes—including geographical location, demographics, and behaviors—are unrelated to variation in incentivized elicitations. Fourth, qualitative self-assessments are no simpler for participants than incentivized elicitations: these questions show a common heuristic of extreme or midpoint responses, especially by individuals with lower cognitive ability.
Keywords: C90; C91; C93; D90; 330; econographics; self-assessments; risk preferences; time preferences; social preferences; preference elicitation; experimental validation